Marriage Law Reform: Efforts in Achieving Gender Equality - Fahmi, Chairul; Hasanah, Uswatun; Yusuf, Yusriaina (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The elimination of child marriage as a social problem in modern Indonesia was a primary motivation for the passage of Law Number 16 of 2019 on Amendments to Law Number 1 of 1974 on Marriage. This law came into effect on January 1, 2019. The purpose of this study is to investigate issues of gender equality between male and female candidates for the roles of bride and groom, which led to the change in the law. The concepts of non-discrimination, equality, and justice all serve as the foundation for various components of the concept of equality. This study is a form of literature review in which the primary data is gathered from secondary sources, particularly legal documents, books, journals, and articles that are linked to the subject matter of this research. According to the findings of the study, the efforts of the government to protect children's rights and ensure that men and women have equal rights, particularly those linked to the minimum age limit for entering into marriage, are a major factor in the modifications that have been made to the Marriage Law. The minimum age limit for entering into marriage is currently set at 18 years old. Therefore, according to the most recent law governing marriage, the minimum age requirement for marriage is 19 years old for both men and women. According to the former Marriage Law, there is therefore no change to the minimum age requirement, which remains the same. Penghapusan perkawinan anak sebagai masalah sosial di Indonesia modern menjadi motivasi utama pengesahan Undang-Undang Nomor 16 Tahun 2019 tentang Perubahan atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Undang-undang ini mulai berlaku pada tanggal 1 Januari 2019. Tujuan dari penelitian ini adalah untuk menyelidiki masalah kesetaraan gender antara calon pria dan wanita, yang menyebabkan perubahan undang-undang tersebut. Konsep non-diskriminasi, kesetaraan, dan keadilan semuanya menjadi dasar bagi berbagai komponen konsep kesetaraan. Studi ini merupakan studi literatur dimana data primer dikumpulkan dari sumber sekunder, terutama dokumen hukum, buku, jurnal, dan artikel yang terkait dengan pokok bahasan penelitian ini. Menurut temuan penelitian, upaya pemerintah untuk melindungi hak-hak anak dan memastikan bahwa laki-laki dan perempuan memiliki hak yang sama, terutama yang terkait dengan batas usia minimum untuk menikah, merupakan faktor utama dalam perubahan yang dilakukan terhadap UU Perkawinan. Batas usia minimum untuk menikah saat ini ditetapkan pada usia 18 tahun. Oleh karena itu, menurut UU Perkawinan hasil perubahan, syarat minimal untuk menikah adalah 19 tahun baik bagi laki-laki maupun perempuan. Menurut UU Perkawinan yang lama, maka tidak ada perubahan syarat usia minimal yang tetap sama.